57 In older people, the association between diabetes medication group and hypoglycaemia, cardiovascular disease, and mortality: prospective primary care-based cohort study 2010–2016. (4th December 2019) - Wallis, Katharine; Wells, Susan; Poppe, Katrina; Selak, Vanessa; Kerse, Ngaire
Abstract : Context: Optimal diabetes care involves balancing the potential benefits of treatment (relief of symptoms of hyperglycaemia and reduction of micro- and macro-vascular complications) against the risks (hypoglycaemia) and burden of treatment. There is uncertainty about the long-term benefits and risks of diabetes treatment in older people. Aim: To determine whether in older people there are differences in hypoglycaemia, cardiovascular disease (CVD) events or mortality according to diabetes medication regimen. Study Design: Prospective cohort study. Setting: Auckland and Northland regions of New Zealand. Participants: People aged 65 years or older dispensed insulin and/or oral diabetes medications in 2010 with a baseline HbA1c measurement. Methods: The cohort was stratified into four sub-cohorts defined by the medication dispensed in the 6 months prior to cohort entry: metformin only, metformin plus other oral hypoglycaemic agents, other oral hypoglycaemic agents only, and any insulin (irrespective of oral agents). Participants were followed to the end of 2016 using linked national hospitalisation and mortality data. ICD-10 coded outcomes were hypoglycaemia-associated hospitalisation, fatal and non-fatal CVD, and all-cause mortality. For each outcome, for the whole cohort and by medication sub-cohort, the time to first event was analysed with Cox models adjusted for age, sex, ethnicity, socioeconomic deprivation, baseline HbA1c, prior CVD, and a modified Charlson comorbidity index. Results: Of the 18, 099 participants, at baseline 7669 (42%) were on metformin only, 4842 (27%) were on metformin and other oral agent/s, 1922 (11%) were on other oral agent/s only, and 3666 (20%) were on insulin. During follow-up, 16% experienced hypoglycaemia-associated hospitalisation, 36% cardiovascular hospitalisation and 31% died (of whom half died from CVD causes). The risk of hypoglycaemia-associated hospitalisation was associated with a high baseline HbA1c 70+mmol/mol, increasing age, Māori and Pacific ethnicity, increasing deprivation, prior CVD, comorbidity burden and all medication groups compared to metformin-only with insulin having an adjusted hazard ratio 11.9, 95% CI 10.3–13.8. The risk of the other outcomes was also associated with age, M&x0101;ori ethnicity, deprivation, comorbidity burden, and all medication groups compared to metformin-only although the magnitude of the difference between insulin and other oral/s was much less, and there was no clear separation in the adjusted survival curves by medication group. Conclusion: After adjusting for multiple risk factors, in older people compared to monotherapy with metformin, insulin and any other oral medications are associated with long-term increased risk of hypoglycaemia-associated hospitalisation with insulin being the strongest predictor. While associated with increased risk of fatal and non-fatal CVD and all-cause mortality, the impact of medication group compared to metformin-only is similar.